Students’ study pressures during the Covid-19 global pandemic: exploration of the effects of workload, self-expectation, grade worriness and despondency on college students in Indonesia - Ardi, Zadrian; Eseadi, Chiedu; Ade, Abdul Halim; Hidayat, Hendra; Guspriadi, Yan (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
Pressure during the learning process is a common thing experienced by students. At some points, this pressure will be beneficial in increasing fighting power and motivation, but on the other hand, high-pressure conditions will affect students' mental health. This condition was also experienced when students entered the learning phase during the Covid-19 pandemic. Although several studies have revealed the effectiveness of distance learning during the pandemic, this study aims to reveal causal factors of learning pressure conditions during the pandemic such that it can trigger the emergence of academic stress. This study involved 750 students spread throughout Indonesia. Data gathering was through the use of a questionnaire with indicators developed from existing measuring tools. Data analysis using Structural Equation Model-Partial Least Square (SEM-PLS) with Model Measurement Analysis (MMA) indicate loading, Cronbach Alpha, composite reliability, Average Variance Extracted (AVE) in fit conditions, and Structural Model testing also demonstrated valid condition and fit. The analysis shows a positive relationship between the predictors of the structural model consisting of self-expectation, despondency, grade worriness, and workload, which impact student learning pressures during the pandemic. There is an effect of workload mediation on the relationship between self-expectation and learning pressure. In reducing and controlling student learning pressures during a pandemic, it is necessary to consider these factors in learning activities.